Effect of biofertilizers on micelial growth and spores germination of plant pathogenic fungi - Tratch, Renato; Bettiol, Wagner (Pesquisa Agropecuaria Brasileira, 1997)
The biofertilizer was produced through anaerobic fermentation of cow manure adding milk, sugar, salts, cow liver parts and bone powder. After 73 days of fermentation it was evaluated the effect on micelial growth of Pythium aphanidermatum, Alternaria solani, Stemphylium solani, Septoria licopersici, Sclerotinia sclerotiorum, Botrytis cinerea, Rhizoctonia solani, Fusarium oxysporum f. sp. phaseoli and spores germination of B. cinerea, A. solani, Hemileia vastatrix and Coleosporium plumierae. In relation to micelial growth inhibition, the growth rate was calculated and it was found that, in general, concentrations over 10% caused a total inhibition of growth for the majority of fungi assayed. In case of spores germination, biofertilizer concentration over 20% has inhibited completely the germination of B. cinerea, over 10% inhibited A. solani, 5 and 1% of C. plumierae and H. vastatrix, respectively. Three different biofertilizers were also tested and one of them was less effective, which was the one produced with manure from confined cows opposed to the others produced with grazing cows.